Fiscal responsibility and budget management act in India a review and recommendations for reform. - Carrasco, Bruno (South Asia working papers., 2017)
The paper reviews the international experience and best practices on fiscal rules, types of rules, introduction of fiscal councils and compares Indias FRBM framework against properties of fiscal frameworks, including fiscal balance, capital spending, optimal debt levels, cyclical considerations, and underlying budget processing and implementation. The paper analyzes various reform options based on quantitative fiscal rule simulations. Finally, the paper presents recommendations on adopting appropriate fiscal rules and targets with clearly defined escape clauses and strengthening the enforcement of fiscal rules.